Absorption Spectra of Pesticide Residue about Imidacloprid in Fruit Juices - Ji1, Rendong; Zhao1, Zhimin; Zhang1, Lin; Ji1, Lei; Zhang1, Jihua; Shen1, Lingbin; Lan1, Xiufeng (Asian Journal of Chemistry, 2013)
The absorption spectra of imidacloprid and the mixed system of imidacloprid and juice (apple, orange and peach juice) were studied. The experimental results show that the most intensive characteristic peak (269 nm) was found in the spectrum of standard solution of imidacloprid. With the increasing amount of imidacloprid in apple juice, absorbance of mixed solution of apple juice and imidacloprid was improved gradually and the phenomenon of blue shift was found about the peak position which was decreased from 281 to 269 nm. Then we obtain the prediction model between the peak wavelength or absorbance and the content of imidacloprid (r2 > 0.99). And the prediction model of imidacloprid content were obtained in orange and peach juice through the same process and the coefficient of determination orange juice was 0.97911 and the coefficient of determination of peach juice was 0.96764. The result proved that it is possible to detect pesticide residues of imidacloprid in fruit juice and it can meet the needs of rapid analysis.